Matrix support in specialized care backed by the care model for chronic conditions: evaluative research - Francielle Renata Danielli Martins Marques; Grazieli Adrieli Rodrigues Pires; Vanessa Denardi Antoniassi Baldissera; Marcelle Paiano; Lígia Carreira; Maria Aparecida Salci (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To analyze the matrix support for health teams in Specialized Outpatient Care, according to the Chronic Conditions Care Model. Method: Qualitative evaluative research, conducted by the Chronic Conditions Care Model, carried out from February to July 2020. For data collection, interviews were carried out with 21 health professionals, assistance observation and document analysis of the service. Data were analyzed by data triangulation, with the aid of the MAXQDA software, respecting all ethical aspects. Results: The matrix support provided approximation between Primary and Secondary Care; implemented case management and qualified comprehensive care for people with chronic conditions. Weaknesses in communication and understanding of the theoretical bases of matrix support were obstacles to the proper implementation of matrix strategies. Final consideration: Matrix support for specialized health teams qualified the professional care given to people with chronic conditions treated at the service.